2021
DOI: 10.1136/bmjopen-2020-047847
|View full text |Cite
|
Sign up to set email alerts
|

Burden of tobacco in Nepal: a systematic analysis from the Global Burden of Disease Study 1990–2017

Abstract: ObjectiveThis study systematically reviews the data extracted from the Global Burden of Disease Study and sets out to assess the age-specific and sex-specific mortality and disability attributable to different forms of tobacco from 1990 to 2017, for Nepal.DesignThis cross-sectional study extracted data from the Institute for Health Metrics and Evaluation’s Global Burden of Disease database, then was quantitatively analysed to show the trends and patterns of prevalence of tobacco use, deaths and disability-adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…These results suggest that a sustainable concerted effort to reduce tobacco consumption should sustain over years to have a substantial impact. Similar findings have been reported elsewhere in the world, such as India 14 , Nepal 15 , and China 16 . Their main measures included legislative and awareness in India, regulatory measures in Nepal, and the Healthy China 2030 Initiative in China.…”
Section: Discussionsupporting
confidence: 90%
“…These results suggest that a sustainable concerted effort to reduce tobacco consumption should sustain over years to have a substantial impact. Similar findings have been reported elsewhere in the world, such as India 14 , Nepal 15 , and China 16 . Their main measures included legislative and awareness in India, regulatory measures in Nepal, and the Healthy China 2030 Initiative in China.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have reported that testosterone has an immunosuppressive effect, whereas oestrogens tend to reinforce immunological hyper-response ( Beery, 2003 ). Additionally, the majority of males have a history of smoking and alcohol consumption ( Fujii et al, 2021 ; Shrestha et al, 2021 ). Smoking and alcohol consumption can aggravate underlying diseases and reduce cardiopulmonary function, which is another possible reason for this observation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that testosterone has an immunosuppressive effect, whereas oestrogens tend to reinforce immunological hyperresponse (Beery, 2003). Additionally, the majority of males have a history of smoking and alcohol consumption (Fujii et al, 2021;Shrestha et al, 2021). Smoking and alcohol consumption can aggravate underlying diseases and reduce cardiopulmonary function, which is another possible reason for this observation.…”
Section: Discussionmentioning
confidence: 99%